1993
DOI: 10.1002/jcla.1860070303
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic significance of increased soluble CD8/CD4 molecules in patients with active systemic lupus erythematosus

Abstract: This study attempted to estimate soluble CD4(sCD4)/CD8(sCD8) molecules in active systemic lupus erythematosus (SLE) patients. Measurements were made by solid-phase enzyme-linked immunosorbent assay. sCD8 or sCD4 molecules were significantly increased in the patients as compared to control subjects. sCD8 correlated with the erythrocyte sedimentation rate. sCD4 correlated with the anti DNA antibody titer, the IgG concentration, and negatively with the complement titer. An association of these molecules with immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Previous studies have found increased levels of serum sCD4 in RA and SLE patients, indicating a relevant link to disease activity [13], [39], [40]. In our analysis of clinical serum samples, significantly higher levels of serum sCD4 were found in RA and SLE patients, but not in those with gout.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies have found increased levels of serum sCD4 in RA and SLE patients, indicating a relevant link to disease activity [13], [39], [40]. In our analysis of clinical serum samples, significantly higher levels of serum sCD4 were found in RA and SLE patients, but not in those with gout.…”
Section: Discussionsupporting
confidence: 48%
“…Leishmania infection, 21 human immunodeficiency virus infection, 22 Sjögren’s syndrome 23 and systemic lupus erythematosus. 24 In these inflammatory diseases, the measured serum sCD4 level could be considered as an index of T‐cell activation. Despite the enthusiasm for studying serum sCD4 in various kinds of autoimmune diseases, there have been no available data regarding sCD4 in BP fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified several cytokines that play important roles in the immunopathogenesis of various immune disorders, such as SLE [19][20][21]. Other compounds, such as soluble interleukin-2 (IL-2) receptor, soluble CD4 and soluble CD8, have also been examined and are considered to play important roles in the aberrant immune function encountered in SLE [22][23][24].…”
Section: Introductionmentioning
confidence: 99%